If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + -34 = 29 Reorder the terms: -34 + x = 29 Solving -34 + x = 29 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '34' to each side of the equation. -34 + 34 + x = 29 + 34 Combine like terms: -34 + 34 = 0 0 + x = 29 + 34 x = 29 + 34 Combine like terms: 29 + 34 = 63 x = 63 Simplifying x = 63
| 6x-2=9x-11 | | x-26=28 | | (18)18= | | 18/18= | | z-14=3 | | 729x^3-343=0 | | 100[0.05(q+7)]= | | 3x+2(x-x)= | | 8-8k=-4 | | 4x+26-2z=46 | | -5.6(3p+5)-1.6(2p-6)= | | 50*50+x*x=90*90 | | pq=6x+56 | | (0.7)3= | | -3b^2+48=0 | | 6s^2+23s+20= | | (q+6)(q+5)= | | (0.09)2= | | 14x^2-17x+4= | | 2x+9=7x-18 | | -4g-7=3g | | 5z=10.5 | | y=5x^3-24x^2+16x | | 3(2+x)=3x+6 | | 6x+6(x+8)=180 | | Y=-3x^2+48x-45 | | 25+8y=10y | | -5.4(2p+4)-1.2(4p-6)= | | 0.4(x+200)=900 | | 3x+2y-7=9 | | x^3+2x^2-13x^2+10x=0 | | 9-6s+s^2= |